1997
DOI: 10.1590/s0074-02761997000400002
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzymes Detect Variation in Populations of Triatoma brasiliensis (Hemiptera: Reduviidae: Triatominae)

Abstract: Triatoma brasiliensis is one of the most important vectors of Chagas disease in the semiarid Lent, 1941 and T. brasiliensis macromelasoma Galvão, 1956. These subspecies differ mainly in their cuticle colour pattern and were regarded as synonyms by Lent and Wygodzinsky (1979) Galvão, 1956. Their descriptions are based on the different chromatic patterns of pronotum, hemelytron and legs. A taxonomic key for the different subspecies can be found in Galvão (1956). These subspecies were synonymized by Lent and Wygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 5 publications
7
52
0
5
Order By: Relevance
“…Nei's genetic distance reaches values corresponding to those found at the interspecific level for other species of Triatominae (Costa et al, 1997a). The greatest distance was obtained between the brasiliensis and melanica populations.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Nei's genetic distance reaches values corresponding to those found at the interspecific level for other species of Triatominae (Costa et al, 1997a). The greatest distance was obtained between the brasiliensis and melanica populations.…”
Section: Introductionsupporting
confidence: 51%
“…Lent & Wygodzinsky (1979) considered these subspecies as synonymous based on the fact that intermediate forms seem frequent. Recently, a fourth chromatic pattern was collected in Juazeiro (Bahia), named as "juazeiro population" (Costa et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…We did not record intermediate forms, reported by Lent and Wygodzinsky (1979). Maybe these intergrading forms could be present in the border lines where crossings among different colour patterns could be occuring; isoenzymatical data (Costa et al 1997) suggested a clear genetic differentiation among these populations of T. brasiliensis, reaching Nei's genetic distance values correspondent to those found at interspecific level, for other phylogenetic related species (Pereira et al 1996).…”
Section: Discussionmentioning
confidence: 94%
“…The characterization of phenotypically diverse populations of T. brasiliensis seemed to represent an exception in that fixed allozyme differences were found between conspecific populations (Costa et al 1997). The alternative view that several distinct taxa were involved was later supported by DNA sequence analysis .…”
Section: Allozyme Electrophoresismentioning
confidence: 99%
“…In general, when clear differences (diagnostic loci in sympatry or large genetic distances in allopatry) were detected between populations, the usual outcome was that more than one taxon was involved, either because of misidentification (e.g., R. colombiensis wrongly identified as R. prolixus) or cryptic speciation (as with T. sordida) , Noireau et al 1998. The characterization of phenotypically diverse populations of T. brasiliensis seemed to represent an exception in that fixed allozyme differences were found between conspecific populations (Costa et al 1997). The alternative view that several distinct taxa were involved was later supported by DNA sequence analysis .…”
Section: Allozyme Electrophoresismentioning
confidence: 99%